Latin American Art: Considerations from a peripheral perspective - Sartor, Mario (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This text proposes a panoramic view of contemporary Latin American art and the main themes of debate where it has been a protagonist. The origins of modernity in the American subcontinent and its complicated relationships with the great dynamic centres of international art are analysed, using Richard McGee Morse and George Kubler as readings. The importance of movements such as indigenism and Mexican muralism is also assessed, in an attempt to correct the prejudices against them. A special section refers to relations with Italian culture, especially the reception given to Latin American art in this European territory.